Business Models in the Sports industry: a literature review as a theoretical approach - Runesi, Salmon; Louk, Michael Johanes Hadiwijaya; Utomo, Andy Widhiya Bayu; Saputra, Sylvana Yaka; Puriana, Ramadhany Hananto (Journal of Sport and Exercise Science, 2025)
Purpose: The sports industry, with its unique blend of commercialization and globalization, has seen rapid growth. The business model in this industry, a complex and crucial aspect, determines the desirability and profitability of various sports entities, including clubs, federations, and sports-based companies. This research, through a literature approach, delves into the distinct business models applied in the sports industry, identifying key trends, challenges, and innovation opportunities. Materials and Methods: The research method used is a literature study and secondary data analysis related to Business Models in the Sports industry. Result: The study's results show that the main factor in the volleyball business's success is the synergy between sports federations, sponsors, and the media in building commercial appeal. Conclusion: This study underscores the necessity of selecting a business model that aligns with the unique characteristics of a sports organization. In the face of globalization and rapid technological advancements, sports organizations must demonstrate adaptability and develop innovative business strategies. The implications of this research include recommendations for stakeholders in the sports industry to focus more on revenue diversification and the adoption of digital technology.